Cadmium and Copper Removal From Aqueous Solutions Using Chitosan-Coated Gasifier Biochar - Burk, Griffin A.; Herath, Amali; Crisler, Glenn B.; Bridges, David; Patel, Shivani; Pittman, Charles U.; Mlsna, Todd (Frontiers in Environmental Science, 2020)
Gasifier (GBC) and Chitosan-Coated Gasifier Biochar (CGBC) derived from pine wood was used to remove Cu2+ and Cd2+ from water. CGBC was made by mixing GBC with aqueous acetic acid chitosan solution followed by treatment with NaOH. Both CGBC and GBC were characterized using FT-IR, scanning electron microscopy (SEM), surface area measurement (BET), elemental analysis (EA), TGA, and point of zero charge. Chitosan accounts for 25% of the weight of the CGBC. TGA showed chitosan decomposes sharply at 225 – 270 °C and then more slowly thereafter. The BET surface areas of GBC and CGBC were 34.1 and 4.61 m2/g, respectively. Batch absorption studies performed at pH values of 2-5 followed Cu2+ and Cd2+ adsorption quantitatively using atomic absorption spectrophotometry (AAS). Sorption was evaluated using the Freundlich, Langmuir, and Sips isotherm models. Cu2+ adsorption on CGBC fit best the Sips model (capacity 111.5 mg/g) and Cd2+ with the Langmuir model (capacity 85.8 mg/g). Langmuir adsorption capacities on GBC were 83.7 and 68.6 mg/g for Cu2+ and Cd2+ respectively. CGBC removed more Cu2+ and Cd2+ than GBC because chitosan modification generates amine coordination sites that enhance metal absorption. Adsorption on CGBC and GBC of both metals followed pseudo-second order kinetics.